The relationship between isometric mid-thigh pull force-time characteristics and swing performance in high-level youth golfers - Sanders, J.; Gould, Z.; Moody, J. (International Journal of Golf Science, 2021)
The production of vertical ground reaction force has been suggested to relate directly to club head speed (CHS) in golfers, providing a rationale for the implementation of strength and conditioning to enhance performance. The aim of the study was to determine the relationship between isometric mid-thigh pull (IMTP) force-time characteristics and measures of swing performance (CHS and Carry) in high-level youth golfers. Thirteen high-level youth golfers selected for their National Squad performed IMTP and swing testing using a TrackMan launch monitor across two testing sessions. Results revealed significant correlations between IMTP Peak Force (PF) and 6-iron Carry (r=0.91, p<0.001), Driver Carry (r=0.91, p<0.001), 6-iron CHS (r=0.89, p<0.001) and Driver CHS (r=0.88, p<0.001). All other variables showed trivial to large non-significant correlations. Findings support the use of the IMTP as a testing tool in high-level youth golfers and emphasise the importance of strength training within this population.